Permanent earthquake‐induced actions in buried pipelines: Numerical modeling and experimental verification. (3rd December 2017) - Sarvanis, Gregory C.; Karamanos, Spyros A.; Vazouras, Polynikis; Mecozzi, Elisabetta; Lucci, Antonio; Dakoulas, Panos
Summary: Buried pipelines are often constructed in seismic and other geohazard areas, where severe ground deformations may induce severe strains in the pipeline. Calculation of those strains is essential for assessing pipeline integrity, and therefore, the development of efficient models accounting for soil‐pipe interaction is required. The present paper is aiming at developing efficient tools for calculating ground‐induced deformation on buried pipelines, often triggered by earthquake action, in the form of fault rupture, liquefaction‐induced lateral spreading, soil subsidence, or landslide. Soil‐pipe interaction is investigated by using advanced numerical tools, which employ solid elements for the soil, shell elements for the pipe, and account for soil‐pipe interaction, supported by large‐scale experiments. Soil‐pipe interaction in axial and transverse directions is evaluated first, using results from special‐purpose experiments and finite element simulations. The comparison between experimental and numerical results offers valuable information on key material parameters, necessary for accurate simulation of soil‐pipe interaction. Furthermore, reference is made to relevant provisions of design recommendations. Using the finite element models, calibrated from these experiments, pipeline performance at seismic‐fault crossings is analyzed, emphasizing on soil‐pipe interaction effects in the axial direction. The second part refers to full‐scale experiments, performed on a unique testing device. These experiments are modeled with the finite element tools to verify their efficiency in simulating soil‐pipe response under landslide or strike‐slip fault movement. The large‐scale experimental results compare very well with the numerical predictions, verifying the capability of the finite element models for accurate prediction of pipeline response under permanent earthquake‐induced ground deformations.